The Level of Strategic Thinking Among School Principals in the Center of Misan Governorate from the Perspective of Their Teachers - Multaka Nasser Jabbar ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The research aimed to identify the level of strategic thinking among school principals in the center of Maysan Governorate from the perspective of their teachers. To achieve the research objective, the researcher used the descriptive-analytical approach, as it was suitable for the research procedures. The research involved all the primary school teachers in the center of Misan Governorate, totaling (13102) teachers. The current research sample included (231) teachers randomly were selected from different schools in the center of the governorate.The researcher used a strategic thinking level scale (prepared by the researcher) with (15) items were distributed across strategic thinking patterns including (holistic, abstract, diagnostic, and planning). After analyzing and interpreting the results, the results indicated that the level of strategic thinking practiced among primary school principals was generally high. The researcher recommended to conduct further studies on the level of strategic thinking practice among school principals in other stages and governorates